DEVELOPMENT OF BIOINFORMATICS BASED DETECTION AND BUILDING MODEL OF THE MSPA GENE IN MYCOLICIBACTERIUM FORTUITUM. - Ramadhani, Najma; Kurniawati, Siti; Pinasti, Roro Titah; Savytri, Diaz Ayu; Makta, Averoes Gibraltar (Faculty of Veterinary Medicine Universitas Brawijaya, 2025)
The mspA gene is a nanopore protein located in the outer membrane of Mycolicibacterium fortuitum, which plays a role in the uptake pathway for hydrophilic nutrient molecules. The MspA gene is extremely stable against denaturation, making it capable for DNA sequencing. The accuracy of DNA sequencing is highly dependent on the selection of primer pairs. This study aims to develop primers and amplification for the mspA gene in Mycolicibacterium fortuitum. These organisms are typically free-living and can be found widely throughout the environment. Mycolicibacterium fortuitum is responsible for infections in both animals and humans, so there must be a specific detection method. One specific detection method that can be applied is Polymerase Chain Reaction (PCR). An important factor in the PCR technique is the presence of specific primers that will be used in the detection process. The method used involves a bioinformatics approach through the NCBI Primer Blast Program on Mycolicibacterium fortuitum strain MF GZ001 with the template strain reference NZ_CP107719.1, and a structural model approach through protein modelling using the template uun.1.A MSPA. The result of our study was successfully generated from comparing ten primers, only three primers were chosen based on the specific criteria. We also found the successful building for 3D modeling protein from 215 amino acids. In conclusion, the primer development for mspA gene detection resulted in a pair of primer and the 3D structure of the protein encoded by the gene.